Predicting team rankings in team handball: The questionable use of on-court performance statistics - Ashkenazi, Y.; Lidor, R.; Arnon, M.; Tenenbaum, G. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
The use of statistical reports to measure on-court performances of team handball players (e.g., number of shots from distances of 6m, 7m, and 9m, turnovers, steals) has become a common practice in professional and amateur leagues. These statistical reports are used by coaches and players to assess defensive and offensive performances demonstrated by the individual player and the entire team during a single game, the entire season, or a number of consecutive seasons. Statistical information on team handball's on-court performances is also used by coaches when preparing the player/team for the upcoming game/s. Quite often, these statistics are used by those professionals who work with the team handball team (e.g., coaches, assistant coaches, and scouts), as well as by journalists representing the written and electronic media, to predict future success and final rankings of the team handball teams.